Questions and answers in the management of children with medulloblastoma over the time. How did we get here? A systematic review - Osuna-Marco, Marta P.; Martín-López, Laura I.; Tejera, Águeda M.; López-Ibor, Blanca (Frontiers in Oncology, 2023)
Introduction: Treatment of children with medulloblastoma (MB) includes surgery, radiation therapy (RT) and chemotherapy (CT). Several treatment protocols and clinical trials have been developed over the time to maximize survival and minimize side effects.Methods: We performed a systematic literature search in May 2023 using PubMed. We selected all clinical trials articles and multicenter studies focusing on MB. We excluded studies focusing exclusively on infants, adults, supratentorial PNETs or refractory/relapsed tumors, studies involving different tumors or different types of PNETs without differentiating survival, studies including <10 cases of MB, solely retrospective studies and those without reference to outcome and/or side effects after a defined treatment.1. The main poor-prognosis factors are: metastatic disease, anaplasia, MYC amplification, age younger than 36 months and some molecular subgroups. The postoperative residual tumor size is controversial.2. MB is a collection of diseases.3. MB is a curable disease at diagnosis, but survival is scarce upon relapse.4. Children should be treated by experienced neurosurgeons and in advanced centers 5. RT is an essential treatment for MB. It should be administered craniospinal, early and without interruptions.6. Craniospinal RT dose could be lowered in some low-risk patients, but these reductions should be done with caution to avoid relapses.This is a provisional file, not the final typeset article 7. Irradiation of the tumor area instead of the entire posterior fossa is safe enough.8. Hyperfractionated RT is not superior to conventional RT 9. Both photon and proton RT are effective.10. CT increases survival, especially in high-risk patients.11. There are multiple drugs effective in MB. The combination of different drugs is appropriate management.12. CT should be administered after RT.13. The specific benefit of concomitant CT to RT is unknown.14. Intensified CT with stem cell rescue has no benefit compared to standard CT regimens.15. The efficacy of intraventricular/intrathecal CT is controversial.16. We should start to think about incorporating targeted therapies in front-line treatment.17. Survivors of MB still have significant side effects.Survival rates of MB improved greatly from 1940-1970, but since then the improvement has been smaller. We should consider introducing targeted therapy as front-line therapy.